2022
DOI: 10.1080/21711976.2022.2040829
|View full text |Cite
|
Sign up to set email alerts
|

Pro-environmental behaviour in China: analysing the impact of attitudinal and contextual factors (Comportamiento proambiental en China: analizando el impacto de los factores actitudinales y contextuales)

Abstract: This research analyses pro-environmental behaviour (considering four categories: transport and mobility, waste management, ecological consumption and activism) according to environmental attitudes and certain contextual factors regarding the neighbourhood of residence. In addition, based on the assumptions of ABC theory, we evaluate the moderating effects of context on the relationship between attitudes and pro-environmental behaviours. The study sample consists of 218 people living in China who completed a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Van Geffen et al (2016) encontraron que las personas con visiones del mundo más débiles proambientalmente muestran indicadores cognitivos que indican un desequilibrio entre lo que es consistente según su visión del mundo y lo que se les presenta mediante estímulos visuales. Zhang et al (2022) indican que diversas variables actitudinales pueden dar cuenta de las cuatro categorías de conducta proambiental: transporte y movilidad, gestión de residuos, consumo ecológico y activismo. Estas cuatro categorías conductuales también reciben la influencia directa de las circunstancias contextuales, que modifican la interacción entre los dos tipos de conductas y las dimensiones actitudinales (gestión de residuos y consumo ecológico).…”
Section: Determinantes Sociodemográficos De La Actitud Ambiental El C...unclassified
See 1 more Smart Citation
“…Van Geffen et al (2016) encontraron que las personas con visiones del mundo más débiles proambientalmente muestran indicadores cognitivos que indican un desequilibrio entre lo que es consistente según su visión del mundo y lo que se les presenta mediante estímulos visuales. Zhang et al (2022) indican que diversas variables actitudinales pueden dar cuenta de las cuatro categorías de conducta proambiental: transporte y movilidad, gestión de residuos, consumo ecológico y activismo. Estas cuatro categorías conductuales también reciben la influencia directa de las circunstancias contextuales, que modifican la interacción entre los dos tipos de conductas y las dimensiones actitudinales (gestión de residuos y consumo ecológico).…”
Section: Determinantes Sociodemográficos De La Actitud Ambiental El C...unclassified
“…Van Geffen et al (2016) found that those with weak pro-environmental worldviews exhibit cognitive indicators of a mismatch between what is consistent with their worldview and what they are presented with within the visual stimuli. For their part, Zhang et al (2022) indicate that several attitudinal variables can account for the four pro-environmental behaviour categories: transport and mobility, waste management, ecological consumption and activism. The four behavioural categories are also directly impacted by contextual circumstances, which modify the interaction between the two types of behaviours and the attitudinal dimensions (waste management and ecological consumption).…”
mentioning
confidence: 99%
“…La mayor parte de estos estudios concluyen que la falta de conciencia ambiental es el obstáculo principal de los visitantes a la hora de apreciar, comprender y valorar el área natural para favorecer la conservación (Ballantyne et al, 2008;Zhang et al, 2022). La importancia de implementar métodos que promuevan la conciencia entre los visitantes ha sido señalada, como destacan estudios anteriores (Du et al, 2019;Parelman y Marconi, 2016).…”
Section: Introductionunclassified